O8 Metric development for tracheostomy suctioning: assessment of face and content validity. (5th November 2017) - Noonan, B; Walsh, N; Healy, S; Dunn, R; O'Grady, M; Manning, M; Gallagher, A; Howson, V
Abstract : Project: Background: Despite the abundance of tracheostomy care guidance available to Health Care Professionals, implementation of good practice remains poor (Zhu et al., 2015). Tracheostomies continue to be associated with serious risks such as hypoxia, respiratory arrest and cardiac arrest (Felton et al., 2014); airway occlusion/obstruction due to tenacious or profuse secretions, mucous plugging, excessive granulation tissue (Zhu et al., 2014); tube displacement or dislodgement (Hettige, 2013); inability to pass suction catheter or insert inner cannula (Pandian et al., 2012); tracheal stenosis (McGrath et al., 2012); infection and aspiration (Durbin, 2010) and tracheal necrosis due to over inflation of cuff (Mitchell, 2013). Aim: To establish the metrics (operational definitions) necessary to characterise tracheostomy suctioning, and to seek consensus from experienced tracheostomy care practitioners on the appropriateness of the steps as well as the errors identified. This forms part of a larger study to determine the effectiveness of proficiency based progression (PBP) training for tracheostomy care on learner performance in a simulated context. Project Description: A process similar to that outlined by Angelo et al. (2015) was implemented. Procedural characterisation involved a task analysis, a deconstruction process and metric identification. Six experienced healthcare practitioners and an experimental psychologist (comprising the Metrics Group) deconstructed the suctioning element of tracheostomy care. Thirteen full-length videos were analysed to identify the essential steps and potential errors. Critical (i.e., more serious) errors were defined as an event or occurrence involving a serious deviation from optimal performance. Results: Sixty three metrics and 9 phases characterising tracheostomy suctioning for a self-ventilating patient were identified. Sixteen steps were identified, 20 procedural errors were specified, with 27 designated sentinel errors. The modified Delphi Panel deliberation created the following changes: 2 metrics were deleted, 1 was added and 5 were modified. Consensus on the resulting suctioning metrics was obtained and face and content validity verified. Conclusions: This phase of a larger Proficiency Based Progression study confirms that a core group of experienced practitioners are able to perform task deconstruction of tracheostomy suctioning for a self-ventilating patient and create unambiguous step and error definitions (metrics) that accurately characterise the essential components of the procedure. Analysis and revision by a larger panel of experienced tracheostomy care practitioners were able to validate the suctioning metrics. Recommendations: The ability to perform task deconstruction and validate the resulting metrics will play a key role in improving tracheostomy care skills training and assessing trainee progression towards proficiency. References: . Angelo RL, Ryu RK, Pedowitz RA, Gallagher AG. Metric development for an arthroscopic Bankart procedure: Assessment of face and content validity. Arthroscopy: The Journal of Arthroscopic & Related Surgery 2015;31(8):1430–1440. . Durbin CG. Tracheostomy: Why, when and how? Respiratory Care 2010;55:1056–1068. . Felton M, Yuan J, Liu C, et al. The trachea collaborative inaugural meeting report 2014. Glasgow: Scotland. . Hettige R, Arora A, Oldfield WLG, et al. Recent developments to improve the standard of tracheostomy care. British Journal of Intensive Care 2013;13(7):77–80. . McGrath BA, Bates L, Atkinson D, et al. Multidisciplinary guidelines for the management of tracheostomy and laryngectomy airway emergencies. Anaesthesia 2012;67:1025–1041. . Mitchell RB, Hussey HM, Setzen G, et al. Clinical consensus statement: Tracheostomy care. Otolaryngology Head Neck Surgery 2013;148:6–20. . Pandian V, Miller CR, Mirski MA, et al. Multidisciplinary team approach in the management of tracheostomy patients. Otolaryngology Head Neck Surgery 2012;147:684–691. . Zhu H, Das P, Woodhouse R, Kubba H. Improving the quality of tracheostomy care. Breathe 2014;10(4), 287–294. . Zhu H, Das P, Robertson DW, et al. Hospitalisations in children with pre-existing tracheostomy: A national perspective. Laryngoscope 2015;125(2):462–468.